White-centered retinal hemorrhage revealing acute leukemia: A case report. (May 2022) - Ben Abdesslem, Nadia; Zaafrane, Nesrine; Ben Abderazek, Atf; Jabri, Ahmed; Mahjoub, Anis; Ben Youssef, Chiraz; Mahjoub, Hachemi; Krifa, Fethi; Mahjoub, Ahmed
Abstract: Retinal manifestations have been described as an inaugural manifestation of acute leukemia. Retinal hemorrhage, and in particular white-centered hemorrhages are among the most frequently observed signs. We report here the case of a 34-year-old Caucasian man with no medical history who presented to our emergency department with a decrease in visual acuity associated with asthenia. Ophthalmological examination revealed bilateral white-centered hemorrhages. The etiological assessment confirmed the diagnosis of acute myeloid leukemia. Whenever Roth spots are found in fundus examination, a complete ophthalmological examination along with a wide etiological investigation must be conducted. Highlights: Roth spots are associated with endocarditis, leukemia, anemia, hypertensive retinopathy, diabetic retinopathy and preeclampsia. A complete ophthalmological examination along with paraclinical exploration must be conducted. Leukemia is one of the most life-threatening diagnoses that can be revealed by white-centered hemorrhages.